The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.alc.0000175040.91007.d0
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning and Working Memory in Fetal Alcohol Spectrum Disorder

Abstract: The goal of this report is to critically review research on executive functioning (EF) and working memory in individuals with fetal alcohol spectrum disorder (FASD). Individuals with FASD exhibit EF deficits in the areas of cognitive flexibility, planning and strategy use, verbal reasoning, some aspects of inhibition, set shifting, fluency, working memory, and, recently, on tests of emotion-related or hot EF. Some researchers have linked prenatal alcohol exposure to abnormalities in the development of the fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
223
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(242 citation statements)
references
References 59 publications
11
223
0
8
Order By: Relevance
“…Additionally, as Dodge's model suggests, neurologically mediated differences in behavioral regulation impact and interact with experience and the development of schemas stored in memory [Dodge, 2006]. There is considerable research indicating that children with PAE have difficulties with behavioral regulation, memory and executive functioning relative to children without prenatal exposure even when other cognitive differences have been statistically controlled [Rasmussen, 2005;Rasmussen et al, 2006;Schonfeld et al, 2006;Kodituwakku, 2007]. Considering the well documented neurocognitive deficits seen in children with FASDs, it would not be surprising for them to fail to develop a benign attributional style and, instead, develop impaired social cognitive processes.…”
Section: Middle Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as Dodge's model suggests, neurologically mediated differences in behavioral regulation impact and interact with experience and the development of schemas stored in memory [Dodge, 2006]. There is considerable research indicating that children with PAE have difficulties with behavioral regulation, memory and executive functioning relative to children without prenatal exposure even when other cognitive differences have been statistically controlled [Rasmussen, 2005;Rasmussen et al, 2006;Schonfeld et al, 2006;Kodituwakku, 2007]. Considering the well documented neurocognitive deficits seen in children with FASDs, it would not be surprising for them to fail to develop a benign attributional style and, instead, develop impaired social cognitive processes.…”
Section: Middle Childhoodmentioning
confidence: 99%
“…Fetal alcohol syndrome (FAS), one of the most severe conditions resulting from in utero alcohol exposure, is defined by a pattern of characteristic facial malformations, growth deficiencies, and neurodevelopmental deficits [Jones and Smith, 1973]. A substantial body of research has documented significant neurocognitive difficulties among individuals with FAS as well as among individuals who have been prenatally exposed to alcohol but do not meet full criteria for FAS [Rasmussen, 2005;Riley and McGee, 2005;Rasmussen et al, 2006;Kodituwakku, 2007;McGee and Riley, 2007;Paley and O'Connor, 2007;Guerri et al, 2009]. This latter group of individuals may be described as having partial FAS (pFAS), alcohol related neurodevelopmental disorder (ARND), or alcohol related birth defects (ARBD) according to the diagnostic categories proposed by the Institute of Medicine [Stratton et al, 1996;Hoyme et al, 2005].…”
mentioning
confidence: 99%
“…Consistently, researchers looking at clinical and community samples, as well as caregivers, have found that individuals prenatally exposed to alcohol may have significant neurobehavioral impairments. In particular, deficits are reported in executive functioning (Rasmussen, 2005), learning, memory, language, intelligence, motor, visual-spatial abilities (see Kodituwakku, 2007Kodituwakku, , 2009Mattson, Crocker, & Nguyen, 2011), and academic achievement (Streissguth et al, 1994). Problems with disrupted school experiences, mental health problems, incarceration and retention in the justice system, as well as inappropriate sexual behaviors and alcohol and drug abuse have also been described (Streissguth, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Die meisten Kinder mit FASD haben Schwächen in den Exekutivfunktionen (Fuglestad et al, 2014;Rasmussen, 2005).…”
Section: Studienlageunclassified